2008
DOI: 10.1007/s12221-008-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of ring yarn unevenness by soft computing approach

Abstract: This paper demonstrates the application of two soft computing approaches namely artificial neural network (ANN) and neural-fuzzy system to forecast the unevenness of ring spun yarns. The cotton fiber properties measured by advanced fiber information system (AFIS) and yarn count have been used as inputs. The prediction accuracy of the ANN and neuralfuzzy models was compared with that of linear regression model. It was found that the prediction performance was very good for all the three models although ANN and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This is attributed to the higher unevenness of finer yarns as compared to their coarser counterpart. Majumdar et al (2008) also reported the use of the ANFIS for the prediction of ring spun yarn unevenness using the cotton fibre properties measured by the advanced fibre information system (AFIS) and yarn count as inputs. ANN and linear regression models were also developed for the comparative evaluation of prediction performance.…”
Section: © Woodhead Publishing Limited 2011mentioning
confidence: 99%
See 2 more Smart Citations
“…This is attributed to the higher unevenness of finer yarns as compared to their coarser counterpart. Majumdar et al (2008) also reported the use of the ANFIS for the prediction of ring spun yarn unevenness using the cotton fibre properties measured by the advanced fibre information system (AFIS) and yarn count as inputs. ANN and linear regression models were also developed for the comparative evaluation of prediction performance.…”
Section: © Woodhead Publishing Limited 2011mentioning
confidence: 99%
“…During roller drafting, short fibres float in between the front and back roller nip and their velocity is totally uncertain. Thus, the short fibres generate 7.5 Effect of fibre length and short fibre content on ring yarn unevenness (source: Majumdar et al, 2008). drafting waves and increase the unevenness of the fibre strand. Figure 7.6 shows the impact of yarn count and short fibre content on yarn unevenness, keeping fibre length constant at mid-level (0.93 inch).…”
Section: Prediction Performance Of Different Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses had proved that artificial neural network models improved the prediction performance with regards to regression models. Majumdar et al 3 demonstrated the application of two soft computing approaches namely artificial neural network and neural-fuzzy system to forecast the unevenness of ring spun yarns. Ghosh et al 4 presented a support vector machine regression approach to forecast the properties of cotton yarns produced on ring and rotor spinning technologies from the fiber properties measured by HVI and AFIS.…”
mentioning
confidence: 99%
“…One or more hidden layers are located between input and output layers. The number of hidden layers and number of hidden layer's neurons vary, depending on the complexity of problem and training dataset' quality and size (Majumdar et al, 2008). A small number of neurons in hidden layers may lead the network to fall into a local minimum, in which case the network does not have sufficient time to learn the dataset's feature.…”
Section: Introductionmentioning
confidence: 99%